Análise imunoistoquímica do CD133, c-MYC e AXL no adenocarcinoma e pólipos colorretais e sua associação prognóstica e clínico-patológica - Rutz, Leticia Elizabeth Augustin Czeczko (2019)
Introduction: Colorectal cancer (RCC) has been extensively molecularly characterized in recent years to provide tools that can allow differentiation of subgroups with different prognostic and therapeutic implications. CD133 is a transmembrane glycoprotein currently considered to be the most robust surface marker of colorectal cancer tumor stem cells. C-MYC is one of the major genes responsible for regulating cell growth and metabolism and its overexpression makes it a potent oncogene. AXL is a receptor tyrosine kinase that in the context of malignancy drives comprehensive processes including epithelial transition to mesenchyme. Objectives: The purpose of this study was to evaluate the prognosis and clinical and pathological characteristics of CD133, c-MYC and AXL in colorectal adenocarcinomas and to associate its positivity with dysplasia and morphology in polyps. Material and Method: The adenocarcinoma group included 122 patients of both genders, who were diagnosed between 2010 and 2015. In the polyp group, 39 colorectal polyps resulting from polypectomies performed in colonoscopies between 2009 and 2012 were studied. Immunohistochemistry was performed for CD133, c-MYC and AXL biomarkers in all samples. Retrospective clinical data was collected and plotted in two data tables. Through TMA (tissue microarray) technique, the tissues were subjected to immunohistochemistry by the peroxidase technique. Clinical-epidemiological information was crossed with the result obtained by immunostaining and its statistical analysis. Results: The adenocarcinoma group had 63 men (51.6%) with a mean age of 61.9 years. There was a distribution of 40 cases in the right colon (34.4%) and 75 in left colon and rectum (61.4%). Most patients had an advanced UICC classification (III and IV) (n = 74). From the total number of patients, 68 (55.7%) died and poorly differentiated tumors and disease progression were found to be independent risk factors for death (p <0.05). The median estimated overall survival time was 30 months. CD133+ (CD133 positive tumors) showed a protective relationship against death in univariate analysis but this relevance did not occur in multivariate analysis. There was an association between c-MYC+ (c-MYC positive tumors) and metastasis to other sites (non-hepatic, pulmonary and peritoneal). AXL had four positive cases, precluding further analysis. There was no significant association between the other characteristics analyzed. In the polyp group there were 31 adenomas (79.5%) and 15 (38.5%) presented high-grade dysplasia. Of the 39 polyps, 35.9% (n=14) scored positive for CD133: 15.4% (n = 6) for c-MYC and 15.4% (n = 6) for AXL. There was no statistically significant association between positive tumors and polyp size, location, type, histological diagnosis and high-grade dysplasia. Moderate agreement was found between the c-MYC and AXL biomarkers due to 28 (71.8%) cases in agreement and 11 (28.2%) cases in disagreement. Conclusion: CD133 is not an independent protective factor against death in colorectal adenocarcinoma, whereas c-MYC is associated with distant metastasis. Polyps showed no association between CD133, c-MYC, AXL and clinico-pathological variables. There is a tendency for c-MYC and AXL to be overexpressed in the same tumor profile.